Etika Bisnis Islam dan Transparansi Transaksi: Studi pada Perdagangan Daging Ayam di Pasar Rakyat - Itsnawati, Try; Zainurridla; Supandi, Ach. Faqih (Lajnah Ta'lif wan Nasyr Nahdlatul Ulama (LTN-NU) Kabupaten Probolinggo, 2025)
This study aims to analyze the implementation of Islamic business ethics principles among chicken meat traders in Duko Timur Village, particularly regarding the practices of honesty, trustworthiness, justice, responsibility, and ihsan in buying and selling activities. The research employs a descriptive qualitative approach through observation, interviews, and documentation to obtain a factual overview of traders’ behavior in their daily economic activities. The findings reveal that the traders have generally implemented Islamic business ethics consistently, such as maintaining transparency in weighing, giving buyers the freedom to determine the quantity of their purchase, and providing friendly and humane service. Religious motivation, especially the belief in the blessing of sustenance, plays a significant role in encouraging these ethical behaviors. The study concludes that sustaining business practices that adhere to sharia principles requires collaboration among traders, consumers, and market managers to develop service standards, strengthen ethical literacy, and create a fair and sustainable market system. These findings are expected to serve as a reference for developing traditional markets based on Islamic economic values.